Epidemiological Investigation of Helicobacter pylori as an Emerging Zoonosis in Matrouh Province, North-West Egypt: A Community Based Cross-sectional Study - Rabah, Ibrahim M.; Nossair, Mohamed A.; Hafez, Elsayed E.; Elkamshishi, Mohamed M.; Khalifa, Eman (Journal of Advanced Veterinary Research, 2023)
Helicobacter pylori is newly emerging bacteria and one of the most common infections worldwide with over one-half of the world is infected with this organism. The aim of this study was to determine the prevalence of H. pylori among sheep, camels, and humans in Matrouh Province, North-West Egypt using H. pylori stool antigen enzyme immunoassay and stool PCR. A total of 250 stool samples were collected from farm animals (sheep and Camels) and humans in Matrouh Province. Samples were examined using H. pylori Stool Antigen Enzyme Immunoassay test and H. pylori 16S rRNA PCR. Statistical analysis was applied using Chi2 and IBM SPSS Statistics 25. The overall prevalence of H. pylori infection in the study by HpSA and PCR were 27.6% and 24.4%, respectively. Based on the results of HpSA test, it was found that the prevalence was 12% and 26% in sheep and camels, respectively, with statistically significant association between the prevalence and locality or age of sheep. Moreover, the prevalence of H. pylori infection in human was 44% by HpSA test with statistically significant association between the prevalence and gender or locality being higher in males than females with greater rural prevalence than urban. On the other hand, there was a non-statistically significant differences between H. pylori prevalence and sex, breed, and health status of examined animals or age, residence, and occupation of enrolled individuals. Conclusively, H. pylori was detected in both animal and human samples is alarming in Matrouh Province. Therefore, there was an urgent need for implementing a proper control program.